Assessment of the influential mechanisms of adolescent risk behaviors and protective and risk factors among high school students in Finnmark, Arctic Norway - Shiho Hansen (PLoS ONE, 2025)
Adolescent risk behaviors, including alcohol use and antisocial behaviors, remain a public health concern in Finnmark, Arctic Norway. However, the mechanisms linking risk and protective factors to these behaviors remain underexplored. This study examines the influence of individual and environmental factors—such as family, peers, school, and local contexts—on adolescent alcohol use and antisocial behaviors. Using data from the 2021 Ungdata survey (N = 2,129 high school students), Partial Least Squares Structural Equation Modeling was applied to identify key associations. The results indicate that unstructured peer interactions, particularly spending evenings with friends, are strongly associated with both alcohol use and antisocial behaviors. In contrast, time spent on online gaming was associated with reduced risk of these behaviors, while social media use was positively linked to alcohol consumption. Experiences of sexual harassment, as well as other co-occurring risk behaviors such as smoking, drug use, bullying, and aggression, were consistently associated with increased engagement in both alcohol use and antisocial behaviors. Family and school environments showed limited associations with alcohol use but were linked to antisocial behaviors. Socioeconomic status and gender were not significantly related to either outcome, while depressive symptoms and religiosity showed selective associations, primarily with alcohol use. The findings underscore the need for peer-oriented preventive strategies and consideration of digital media exposure in addressing adolescent alcohol use and antisocial behavior. Future research should incorporate ethnicity-related variables to enhance contextual understanding of adolescent behaviors in the Finnmark region.